New dimensions in shopping centers and stores - Redstone, Louis G. (New York : McGraw Hill Education, 1973)
This book gives today's developer an opportunity to review his thinking in a variety of new and productive channels. The ideas he can bring to bear to update existing centers are particularly helpful, for they will not only strengthen present centers but also help ensure the success of future operations.
Foreword -- Preface -- Acknowledgments -- Introduction -- 1. Suburban Shopping Centers -- 2. Implementation -- 3. A survey of significant centers -- 4. Store interiors -- 5. Reconversion and preservation -- 6. Emerging new developments in shopping environments -- Index.
Includes index.
Keywords: SHOPPING CENTERS